FROM CULTURAL GENES TO SMART LIGHTING DESIGN: MODERN TRANSLATION OF COMMERCIAL LANTERNS FROM THE SONG DYNASTY - Guangpu , Lu; Haifeng, Lu (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2025)
Integrating historical cultural elements into contemporary smart lighting design presents a challenge, as it requires balancing innovation with heritage preservation. This study focused on Song Dynasty commercial luminaires and aims to: (1) investigate the formal characteristics of these luminaires through design archaeology, revealing their balance of standardization and personalization; (2) develop a model for translating traditional cultural elements into modern lighting design; and (3) propose a methodology for integrating smart lighting and neo-consumption trends, recontextualizing cultural elements in contemporary design. Through analysis of 42 Song paintings, 17 textual records, and 23 archaeological artifacts, this study revealed the integration of form and function in the commercial lighting systems of the Song Dynasty through archaeological design analysis, highlighting the intersection of historical and modern design. The findings showed that Song Dynasty lighting fixtures were not only practical tools but also cultural symbols, encompassing transformations in materials, structures, functions, and meanings. Using the tri-axial translation model (form-function-culture), the study translated design elements from traditional Song Dynasty lighting into contemporary lighting design, exploring how traditional culture can be applied in modern design. Additionally, the research introduced a four-stage evolutionary methodology that integrates cultural gene extraction, design encoding, contemporary mapping, and user decoding, achieving an organic fusion of traditional heritage with smart lighting technologies, promoting the inheritance and innovation of Song Dynasty cultural heritage in modern design. The findings highlighted that successful cultural translation involves both modernizing forms and reawakening cultural memory. This work provided a scalable methodology for designers to balance heritage preservation with innovation, offering tools for creating lighting systems that connect emotionally while meeting contemporary needs. By recontextualizing Song design principles, the study promoted sustainable, human-centric smart lighting, demonstrating that ancient wisdom can guide future design practices.